P1070ONLINE HIGH-VOLUME HEMODIAFILTRATION REDUCES PRE-DIALYSIS LEVELS OF INDOXYL SULFATE COMPARED TO HIGH-FLUX HEMODIALYSIS: RESULTS FROM HDFIT MULTICENTRIC RANDOMIZED CONTROLLED TRIAL. (6th June 2020) - Lima, Jordana; Guedes, Murilo; Rodrigues, Silvia; Flórido, Ana Clara; Barra, Ana Beatriz; Canziani, Maria Eugênia; Cuvello, Américo; Poli De Figueiredo, Carlos Eduardo; Pecoits-Filho, Roberto; Nakao, Lia
Abstract: Background and Aims: Online High-Volume Hemodiafiltration (OL-HDF) combines convective and diffusive clearances and is associated with better outcomes compared to standard hemodialysis (HD). Although HDF has been shown to improve the clearance and pre-dialysis concentration of middle size uremic toxins, little is known about its effect on concentration of protein-bound uremic toxins (PBUT), particularly in comparison to high-flux HD. Here, we investigated whether high-volume post-dilution OL-HDF impacts pre-dialysis plasma levels of PBUT indoxyl sulfate (IxS), p -cresyl sulfate (pCS) and indole 3-acetic acid (IAA) compared to high-flux HD over time, since accumulation of these PBUT has been associated with increased overall mortality of CKD patients. Method: This is post hoc analysis of the multicentric randomized controlled trial (RCT) studying the impact of post-dilution high-volume OL-HDF versus high-flux HD on measured physical activity (HDFit - clinicalTrials.gov: NCT02787161), which included clinically stable HD patients with a vintage >3 to <24 months. Total plasma levels of IxS, pCS and IAA were determined by high performance liquid chromatography (HPLC) with fluorescence detection at baseline, 3 and 6 months. The difference between HDF and HD in respect to changes in the PBUT concentrations during the follow up, analyzed using linear mixed effect models, was compared. Results are presented as mean differences between groups in the change from baseline along with 95% confidence intervals (CI). Results: 193 patients (mean age 53 years old, 70% males and 60% white – no differences between groups) were analyzed. There were no differences between HD and OL-HDF groups regarding clinical and biochemical characteristics at the baseline. In the OL-HDF group, 99% of patients achieved a convective volume higher than 22 L and both groups had similar dialysis session duration and blood flows throughout the follow up. The mean differences (95% CI) in concentrations over time for PBUTs among HDF and HD groups are shown in Figure 1. HDF group presented a significantly lower trajectory of IxS levels and a lower trajectory of pCS levels than HD group. Trajectories of IAA levels were not different between groups. Conclusion: OL-HDF reduced the pre-dialysis concentration of IxS and pCS through 6 months-period compared to high-flux HD.